EVALUASI SIMPANG UTAMA KORIDOR SELATAN KOTA SEMARANG STUDI KASUS SIMPANG BANYUMANIK - Nugroho, Untoro (Semarang State University, 2011)
Abstrak: The position of SemarangÃÂ reviewedÃÂ in national andÃÂ regional scaleÃÂ is very strategic,ÃÂ theimpacts ofÃÂ traffic growth are sustainedÃÂ locally and are quiteÃÂ large. That growthÃÂ trafficÃÂ flows should be assessedÃÂ continuouslyÃÂ so asÃÂ to avoid negativeÃÂ impacts. The pattern ofÃÂ trafficÃÂ flowsÃÂ in aÃÂ road section can be seen from the intersection arrangement pattern that is on the segment. Parameters studied include:ÃÂ the number of vehicles out of each arm, current conditions andÃÂ time of the signal. ThisÃÂ analysisÃÂ includes:ÃÂ theÃÂ basicÃÂ saturationÃÂ flow,ÃÂ trafficÃÂ flow,ÃÂ cycleÃÂ time,ÃÂ greenÃÂ time,ÃÂ capacity, degree of saturation and traffic behavior. From the results of research on the signalized intersection atÃÂ theÃÂ intersection Banyumanik, obtained byÃÂ the basic saturationÃÂ flow onÃÂ the northern approach of 5310 pcu/h, east of 3060 pcu/h, south of 4740 pcu/h. Saturation flow rate on the northern approach of 4117 pcu/h, east of 2100 pcu/h, south of 4064 pcu/h. Comparison ofÃÂ the currentÃÂ intersection of 0.857. greenÃÂ time of 161 seconds. Capacity onÃÂ the northern approach of 2474 pcu/h, east of 681 pcu/h, south of 2442 pcu/h. Degree of Saturation onÃÂ the northern approach of 0.7284 pcu/h, east .9261 pcu/h, south of 0.9261 pcu/h. The number of queues on the approach north of 58 pcu, pcu 32 east, south 96.3 pcu. Long queues at the northern approach of 180 meters, 178 meters east, south 294ÃÂ yards.ÃÂ TheÃÂ numberÃÂ ofÃÂ stoppedÃÂ vehiclesÃÂ throughoutÃÂ intersectionsÃÂ 0.80ÃÂ stop/pcu.Tundaan crossingÃÂ byÃÂ anÃÂ averageÃÂ ofÃÂ 40.76ÃÂ sec/pcu.ÃÂ TheÃÂ amountÃÂ ofÃÂ capacityÃÂ andÃÂ degreeÃÂ ofÃÂ saturationÃÂ is almost past the recommended limit, so that wide approach needs to change. Keywords:ÃÂ evaluation, optimization, intersection, Banyumanik ÃÂ Abstrak:ÃÂ PosisiÃÂ kotaÃÂ SemarangÃÂ ditinjauÃÂ dalamÃÂ skalaÃÂ nasional maupunÃÂ regionalÃÂ sangatÃÂ strategis akan menimbulkanÃÂ dampakÃÂ pertumbuhanÃÂ laluÃÂ lintasÃÂ yangÃÂ bersifatÃÂ lokal maupunÃÂ menerusÃÂ yang cukup besar. PertumbuhanÃÂ laluÃÂ lintas yang cukup besar menghasilkan arusÃÂ laluÃÂ lintas yang harus dikajiÃÂ terusÃÂ menerusÃÂ sehinggaÃÂ tidakÃÂ menimbulkanÃÂ dampakÃÂ negatif.ÃÂ ArusÃÂ laluÃÂ lintasÃÂ yangÃÂ cukup besarÃÂ tanpaÃÂ disertaiÃÂ pengaturanÃÂ polaÃÂ laluÃÂ lintasÃÂ yangÃÂ sesuaiÃÂ akan menyebabkanÃÂ tundaanÃÂ yang cukupÃÂ lama dan antrian yang cukup panjang. Pola arusÃÂ laluÃÂ lintas suatu ruasÃÂ jalan dapat kitaÃÂ lihat dariÃÂ polaÃÂ pengaturanÃÂ simpangÃÂ yangÃÂ beradaÃÂ padaÃÂ ruasÃÂ tersebut.ÃÂ ParameterÃÂ yangÃÂ diteliti eliputi jumlahÃÂ kendaraanÃÂ yangÃÂ keluarÃÂ dari masing.masingÃÂ lengan,ÃÂ kondisiÃÂ saatÃÂ iniÃÂ dan waktuÃÂ sinyalnya. Analisis ini meliputi : arus jenuh dasar, arus lalu lintas, waktu siklus, waktu hijau, kapasitas, derajat kejenuhan dan perilakuÃÂ laluÃÂ lintas. Dari hasil penelitian pada simpang bersinyal di persimpangan banyumanik, diperoleh arusÃÂ jenuh dasar pada pendekat utara sebesar 5310 smp/jam,ÃÂ timur 3060 smp/jam,ÃÂ selatanÃÂ 4740ÃÂ smp/jam.ÃÂ NilaiÃÂ arusÃÂ jenuhÃÂ padaÃÂ pendekatÃÂ utaraÃÂ sebesarÃÂ 4117 smp/jam, timurÃÂ 2100ÃÂ smp/jam,ÃÂ selatanÃÂ 4064ÃÂ smp/jam.ÃÂ PerbandinganÃÂ arusÃÂ simpangÃÂ sebesarÃÂ 0,857.ÃÂ waktu hijauÃÂ sebesarÃÂ 161ÃÂ detik.ÃÂ KapasitasÃÂ padaÃÂ pendekatÃÂ utaraÃÂ sebesarÃÂ 2474ÃÂ smp/jam,ÃÂ timurÃÂ 681 smp/jam, selatan 2442 smp/jam. Derajat Kejenuhan pada pendekat utara sebesar 0,7284 smp/jam, timur 0,9261 smp/jam, selatan 0,9261 smp/jam. Jumlah antrian pada pendekat utara sebesar 58 smp,ÃÂ timur 32 smp, selatan 96,3 smp. Panjang antrian pada pendekat utara sebesar 180 meter, timurÃÂ 178ÃÂ meter,ÃÂ selatanÃÂ 294ÃÂ meter.ÃÂ JumlahÃÂ kendaraanÃÂ terhentiÃÂ seluruhÃÂ simpangÃÂ 0,80 stop/smp.Tundaan persimpangan rata.rata sebesar 40,76 det/smp. Besarnya kapasitas dan derajat kejenuhan hampir melewati batas yang disarankan, sehingga perlu perubahan lebar pendekat. Kata kunci : evaluasi, optimalisasi, simpang, Banyumanik